Upaya Peningkatan UMKM di Bidang Barang dan Jasa Berupa Kreativitas Buket Dengan Pemanfaatan Pemasaran Metode Teknologi - Mintawati, Hesri; Desianti, Lisa Chandrasari; Kharisma , Kharisma; Simangunsong, Bonse Aris Mandala Putra; Handayani, Nur Rita (JUDICIOUS, 2025)
Micro and small businesses are one of the sectors that have an important role in the Indonesian economy. In this digital area, technology has enabled MKM to expand market reach and increase efficiency in various aspects of business, including marketing varied flower bouquets that can be developed according to the creativity of the maker. adding various contents and adding items that consumers want. This research uses a qualitative interview method with a case study approach. With competent interview and information methods, research is carried out to determine the value of each variable, either one variable or an independent one without creating a room or comparing the variables. others. Thank you for being chosen by Hai Bukit. The operation is in a fairly strategic location, contains and is neat, has a building large enough to accommodate all the high bouquet equipment, holds training on how to make bouquets, the ingredients used are materials that comply with quality standards and do not harm the equipment. used in good condition, production facilities store the necessary materials in a room that is kept clean. This journal discusses efforts to improve micro, small and medium enterprises in the field of goods and services, especially in terms of creativity in making bouquets. One of the strategies used is to utilize technology in This marketing activity is carried out to expand the marketing period and increase the effectiveness of sales of bouquet products